Pengaruh Pengalaman Kerja, Kompensasi dan Kepuasan KaryawanTerhadap Prestasi Kerja Karyawan Studi pada Perusahaan Umum Daerah Air Minum Tirta Projotamansari Kabupaten Bantul - Risky Siska Prajawati; Kusuma Chandra Kirana; Epsilandri Septyarini (Universitas Batanghari Jambi, 2023)
Companies in the future expect that the businesses they create will have high profits. In addition, the company also expects above average work performance from its employees in the work area. To achieve a rapidly growing company and excellent work performance, the existence of a company really needs a part of human resources. At the Tirta Projotamansari Regional Drinking Water Company in the Bantul Regency, the purpose of this study is to determine the effect of work experience on employee performance, compensation on employee performance, and satisfaction on employee performance, as well as the combined effect of work experience, compensation, and satisfaction on employee performance. The population and samples used in this study were all employees, totaling 60 employees. Because the total number of employees at the Tirta Projotamansari Regional Water Supply Company, Bantul Regency, totaled 60 employees, all employees were taken as a sample, using a saturated sampling technique. using questionnaires as a method of data collection. While multiple linear regression analysis is used for data analysis, and it is supported by the T and F tests. The multicollinearity test, heteroscedasticity test, and normality test make up the traditional assumption test. The research test's findings indicate that job satisfaction and job experience both have positive and significant effects on employee performance. Work compensation also has a positive and significant impact on employee performance. This demonstrates that the variables of work experience, compensation, and employee job satisfaction all influence employee performance in a positive way at the same time.